IMPLEMENTASI MEDIASI PENAL MENGGUNAKAN PENDEKATAN HUKUM ADAT PADA MASYARAKAT ADAT DAYAK HIBUN - Soa, Alfonsus Hendri; Ismawati, Sri (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The development of globalization and the current standard of human life cannot be matched by the existing law enforcement process (human development is dynamic while law is static). So is the emergence of problems that occur related to existing law enforcement, especially criminal law enforcement through the criminal court system. The problem that arises is the number of cases in lawsuits and the capacity of the penitentiary. To eliminate this problem, it is necessary to think about seeking a settlement of legal issues outside the existing justice system (alternative dispute resolution) and one of the efforts that can be made is the application of customary law as a step to reconcile the disputing parties. The aim is that the disputing parties can resolve the problem with their own awareness and prioritize mutual understanding and respect for the rights of victims and perpetrators. As is known in customary law, namely efforts to resolve conflicts and restore balance.